Penerapan Model Waterfall pada Sistem Informasi Akuntansi Pembayaran Upah Buruh Sadap Getah - Ramdhani, L S; Luthfiyani, A; Afriani, Y (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
Sap tapping is an activity of obtaining sap with the Â½ spiral incision technique from top left to bottom right. This activity became one of the choices for the livelihoods of the Indonesian people because Indonesia is the second-largest sap-producing country in the world. Perum Perhutani Regional Division of West Java and Banten is a work unit that manages forests and manages wage payments. The wage payment system used by Perhutani Corporation is still carried out conventionally by recording attendance lists, crop yields, and for reports still carried out by recapitating the data in the previous record so that it is possible that during the process an error occurs in recording and the report becomes less accurate . For that we need a system that supports the payment of labor wages and sap that can facilitate the payment system. So in this study a web-based latex tapping payment system will be built by applying the waterfall model so that it becomes a solution to the problem and can provide convenience to the service of the tapping wage payment system.